Predictive value of biomechanical mapping for pelvic organ prolapse surgery - Egorov, Vladimir (Female Pelvic Med Reconstr Surg, 2021)
OBJECTIVE: This study examined changes in pelvic floor support structure and function after urogynecological surgery. METHODS: This multisite clinical study was designed to explore changes in tissue elasticity, pelvic support, and certain functions (contractive strength, muscle relaxation speed, muscle motility) after pelvic organ prolapse (POP) surgery. A biomechanical mapping of the pelvic floor was performed before and 4 to 6 months after the surgery. The biomechanical data for 52 parameters were acquired by vaginal tactile imaging for manually applied deflection pressures to vaginal walls and pelvic muscle contractions. The two-sample t-test (p<0.05) was employed to test the null hypothesis that the data in Group 1 (positive parameter change after surgery) and Group 2 (negative parameter change after surgery) belonged to the same distribution. RESULTS: 78 subjects with 255 surgical procedures were analyzed across five participating clinical sites. All 52 t-tests for Group 1 versus Group 2 had p-value in the range form 4.0*10(−10) to 4.3*10(−2) associating all of the 52 parameter changes after surgery with the pre-surgical conditions. The p-value of before and after surgery correlation ranged from 3.7*10(−18) to 1.6*10(−2) for 50 of 52 tests; with Pearson correlation coefficient ranging from−0.79 to−-0.27. Thus, vaginal tactile imaging parameters strongly correlated weak pelvic floor pre-surgery with the positive POP surgery outcome of improved biomechanical properties. CONCLUSIONS: POP surgery, in general, improves the biomechanical conditions and integrity of the weak pelvic floor. The proposed biomechanical parameters can predict changes resulting from POP surgery.